Exploring the Impact of Literacy Rate, Health, and Women's Empowerment on Women’s Labor Participation Rate in OIC Member Countries - Sari, Rosita Milenia; Aisyah, Siti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to explore the influence of literacy rate, women's involvement in parliament, fertility rates, and female life expectancy on the female labor participation rate in member countries of the Organization of Islamic Cooperation (OIC). The study employs panel data analysis methods for 20 OIC member countries spanning from 2019 to 2021, utilizing data from the World Bank. The data is processed using Eviews 12 software. Findings from the Fixed Effects Model (FEM) approach indicate that women's participation in parliament harms the female labor participation rate. However, literacy rate, fertility rate, and female life expectancy do not significantly affect the female labor participation rate. Based on the research outcomes, governments should evaluate the causes of the declining female workforce participation rate, engage in dialogue with various stakeholders, and formulate policies that support women's involvement without compromising their participation in the workforce. Additionally, strengthening family support policies, promoting gender equality in parliament, and enhancing women's financial literacy are essential measures.